Implementation of the BLU Policy at the National Gallery of Indonesia: Financing Model and Public–Private Partnership in Its Art Exhibitions 2024–2025 - dewi, Citra Smara; Nurjadin, Indira Estiyanti; Adnyana, I Wayan; Ramadhana, Rizki Ayu (Mudra Jurnal Seni Budaya, 2025)
This study examines the management of the National Gallery of Indonesia (Galeri Nasional Indonesia/GNI) in its transition into a Public Service Agency (Badan Layanan Umum/BLU). GNI was selected for this study as a state cultural institution that holds both national and international art exhibitions, potentially playing a role as a benchmark of contemporary Indonesian art. The transformation marks a significant shift towards an entrepreneurial spirit in institutional performance, directly impacting the management of art exhibitions. The study aims to explain and analyze the implementation of the BLU policy in improving GNI’s management while identifying internal and external challenges and opportunities. This study's novelty lies in using two case studies—Lini Natalini Widhiasi: Infinity Yin and Yang (2024) and Arkiv Vilmansa: Semesta Arkiv (2025)—as representations of the BLU implementation in practice. It employs a descriptive qualitative method with the theoretical framework of institutional entrepreneurship. The findings indicate that the BLU policy stimulates GNI to develop a more collaborative, innovative, and entrepreneurship-oriented management, which should be further strengthened through public-private partnership strategies and diversified funding sources.